Evaluation of the need for chest X‐rays in the management of asymptomatic, intraluminal vascular access device occlusion in childhood cancer. Issue 7 (13th December 2016) - Stammers, David; Connolly, Bairbre; Brandão, Leonardo R.; Zupanec, Sue; Gupta, Sumit
Abstract: Background: Venous access device (VAD) occlusion from intraluminal thrombus is a common complication during childhood cancer treatment. Current practice at many institutions is to assess VAD position with a chest X‐ray (CXR) prior to intraluminal administration of tissue plasminogen activator (tPA). We aimed to determine the utility of this practice. Procedure: A retrospective chart review of children with newly diagnosed cancer with a VAD, treated at The Hospital for Sick Children between 2010 and 2011, was performed. Episodes of line occlusion were identified both by reviewing patient CXRs for indication and identifying tPA doses dispensed. These episodes were reviewed to determine whether CXR findings resulted in management other than tPA. Cases in which the X‐ray resulted in a change in management were further reviewed to determine whether administration of tPA could have resulted in potential patient harm. Results: A total of 330 patients with newly diagnosed cancer with VADs were identified. Eighty‐five (25.8%) patients experienced 123 episodes of VAD occlusion. VAD occlusions occurred more frequently in patients with tunneled external central venous lines (16/39, 41.5%) and peripherally inserted central catheters (PICC) (27/73, 37.0%) versus PORT (42/216, 19.4%; P = 0.001). There were nine (8.1%) episodes of VAD occlusion evaluated with a CXR in which the findings led to a change in management other than administering tPA. In each case, multiple specialists independently concluded that administration of tPA would have been unlikely to cause patient harm. Conclusion: Routine CXRs prior to the administration of tPA for asymptomatic VAD occlusion can safely be omitted.